IMPLEMENTASI KEBIJAKAN PEMBERIAN INSENTIF LAUK PAUK DI UNIVERSITAS TADULAKO - Indriasari, Margareta Yenni (Katalogis, 2015)
This study aims to identify and study the Policy Implementation Incentives Lauk Pauk at the University Tadulako. The research method is qualitative research, with informants of 9 (nine), informants were selected based on purposive. Collecting data in this study begins with the observation (observation), interviews, and documentation. The results of the study explained that, Policy Implementation Incentives Lauk Pauk at the University Tadulako not going well